Allelochemical effect of gramine under temperature stress and impact on fat transesterification. Issue 5 (28th May 2021) - Canton, Michael C.; Omar Holguin, F.; Gard, Charlotte C.; Boeing, Wiebke J.
ABSTRACT: Invading microorganisms can hinder productivity of biofuel algae cultures. We utilise allelochemical gramine as a model to better understand allelopathic effects against Chlorella sorokiniana and invasive alga Coelastrella sp. Coelastrella itself inhibits C. sorokiniana via allelopathy. Both algae were exposed to 0, 4, 8, 16, 32, 64 mg gramine L −1 ( n  = 8) in wellplates at 18, 25 and 32°C to observe temperature effects on gramine's allelopathic influence. We also grew C. sorokiniana in 500 mL flasks ( n  = 3) in 0, 4, 8 and 16 mg gramine L −1 at 25°C to obtain enough biomass to measure fatty acid content. Growth was estimated by measuring optical density at 750 nm and fatty acid content of flask-grown algae via high-lipid performance chromatography (HLPC) after 30 days. Gramine impacted both algae species most strongly, even at low gramine dosages, when grown under sub-optimal temperatures (18 and 32°C). At 25°C, only the highest gramine concentration showed a significant reduction in C. sorokiniana growth compared to other treatments. Gramine concentrations above 16 mg L −1 significantly impacted Coelastrella. Gramine effected algae growth over only a few days. Low concentrations of gramine (<16 mg L −1 ) were not effective stressors to increase lipid accumulation.